The challenge of concomitant infections in the coronavirus disease 2019 pandemic era : severe acute respiratory syndrome coronavirus 2 infection in a patient with chronic Chagas disease and dimorphic leprosy - Kurizky, Patricia Shu (2020)
Coronavirus disease 2019 (COVID-19) was first officially described in Brazil on February 26th, 2020. The accumulation of reports of concomitant infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and pathogens that cause diseases endemic to tropical countries, such as dengue and chikungunya fever, has started to draw attention. Chagas disease and leprosy remain public health problems in many developing countries, such as Brazil. In this manuscript, we describe a case of concomitant leprosy, Chagas disease, and COVID-19, highlighting the cutaneous manifestations of SARS-CoV-2 infection and the clinical behavior of household contacts who previously received prophylactic Bacillus Calmette-Guérin vaccines.